Preparative Scale MS-Guided Isolation of Bioactive Compounds Using High-Resolution Flash Chromatography: Antifungals from Chiloscyphus polyanthos as a Case Study - Azzollini, Antonio; Favre-Godal, Quentin; Zhang, Jiaozhen; Marcourt, Laurence; Ebrahimi, Samad Nejad; Wang, Shuqi; Fan, Peihong; Lou, Hongxiang; Guillarme, Davy; Queiroz, Emerson Ferreira; Wolfender, Jean-Luc (Planta Medica, 2016)
In natural product research, the efficient purification of molecules from large amounts of complex extracts is a key element. In this regard, an integrative strategy for efficient MS-guided isolation of antifungal compounds has been developed. First, off-line HPLC antifungal activity-based profiling and HPLC-PDA-MS profiling were used to localize the compounds of interest on the analytical scale. Then, the analytical gradient was geometrically transferred to the flash chromatographic level. Finally, an MS-triggered isolation of the localized bioactive molecules was realized using high-resolution flash chromatographic columns (15 µm spherical particles) coupled to a single quadrupole mass spectrometer via a splitter system. This isolation strategy was applied for the MS-targeted purification of antifungal principles from the liverwort Chiloscyphus polyanthos. This rational methodology has high potential for the targeted large-scale purification of bioactive compounds, avoiding the need to repeat a given bioassay at each isolation step. Seven sesquiterpene lactones were isolated, of which five were found to be bioactive and one was reported as a new compound. The absolute configuration of some compounds was established for the first time by electronic circular dichroism spectroscopy.
Keywords: Chiloscyphus polyanthos; Geocalycaceae; MS-guided isolation; flash chromatography; antifungal compounds